Pandemics of the century: COVID-19 and impacts on HIV/AIDS monitoring in Brazil (Research, Society and Development, 2023)
Human Immunodeficiency Virus (HIV) infection, from the 1980s to the present day, has grown exponentially worldwide. According to data from the HIV/AIDS epidemiological bulletin, in Brazil, in 2020, 32,701 new cases of HIV were diagnosed and 10,417 deaths due to the underlying cause of AIDS were recorded in that same period. At the same time, in 2020, WHO officially declared that COVID-19 is a pandemic disease, which resulted in changes in the routine of the entire world population, including People living with HIV (PLHIV). The study aimed to compare data related to HIV between the years 2019 and 2020 in Brazil, in the context of the COVID-19 pandemic. A quantitative, descriptive and cross-sectional study was carried out, with data obtained from the epidemiological indicators panel of the Department of Diseases, Chronic Conditions and Sexually Transmitted Infections (DCCI). According to the data analyzed, there was a decline in all the variables analyzed in the five Brazilian regions - antiretroviral therapy Dispensation (ART), PLHIV who started ART, CD4 Tests and Viral Load -, in the comparison between the years 2019 and 2020. Therefore, the impacts of the COVID-19 pandemic stimulated the decline in continued care, reception and prevention against HIV, being a counterpoint to national and global policies that seek to reduce transmission of the virus and improve the quality of life of PLHIV/AIDS.